If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+11=-2x-21
We move all terms to the left:
2x+11-(-2x-21)=0
We get rid of parentheses
2x+2x+21+11=0
We add all the numbers together, and all the variables
4x+32=0
We move all terms containing x to the left, all other terms to the right
4x=-32
x=-32/4
x=-8
| 8f-3+7=34 | | -5(2x-3)=2(x-13)-7 | | 14=-4+2z | | 2x+5(2x-5)=71 | | 5y/3=2y/3 | | 2+2x=3(-x+4)-20 | | 7x-9=8x-10 | | 5y/3-5/3=2y/3-5/3 | | 7y-9y+1=5 | | 4=k/2=-3 | | 16x-53=12x-37 | | /145=z/25 | | 2x+3-1=-x+8 | | /145=z25 | | 7y-9y=1=5 | | 2x+2=1x+10 | | 19a-98=14a-63 | | -52=4-8u | | 9x+72=4x+122= | | w+36=2w+29 | | 4b-59=2b-17 | | 11.02+0.8v=-0.7v−16.88 | | t=3t-62 | | s=6s-35 | | 9k=11k+14 | | r−15.9=−2.4 | | x=(109.61x+8557.7)-8557.7/109.61 | | 7t-50=10t-86 | | -19-6p=-19p+20 | | 6=-2-2x=10 | | z-10=2z-63 | | 8/3c-2=2/3c−12 |